2008
DOI: 10.1126/science.1151844
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the Transcription Factor Th-POK by Runx Complexes in Cytotoxic T Cell Development

Abstract: Mouse CD4+CD8+ double-positive (DP) thymocytes differentiate into CD4+ helper-lineage cells upon expression of the transcription factor Th-POK but commit to the CD8+ cytotoxic lineage in its absence. We report the redirected differentiation of class I-restricted thymocytes into CD4+CD8- helper-like T cells upon loss of Runx transcription factor complexes. A Runx-binding sequence within the Th-POK locus acts as a transcriptional silencer that is essential for Th-POK repression and for development of CD8+ T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
353
2
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(379 citation statements)
references
References 21 publications
11
353
2
1
Order By: Relevance
“…Thus, enhancer activity in the DRE has been supposed to be responsible for early Thpok induction. Interestingly, however, previous studies demonstrated that the DRE also possesses a transcriptional silencer activity that represses expression of reporter transgene as well as the Thpok gene in cytotoxic lineage cells (4,5). Thus, the silencer activity in the DRE (referred to as the Thpok silencer in this study) is essential to limit Thpok expression to helper lineage T cells.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Thus, enhancer activity in the DRE has been supposed to be responsible for early Thpok induction. Interestingly, however, previous studies demonstrated that the DRE also possesses a transcriptional silencer activity that represses expression of reporter transgene as well as the Thpok gene in cytotoxic lineage cells (4,5). Thus, the silencer activity in the DRE (referred to as the Thpok silencer in this study) is essential to limit Thpok expression to helper lineage T cells.…”
mentioning
confidence: 83%
“…Preparation of chromatin DNA and primers for the PE were previously described (5). Abs used are control IgG (SC-2025) and anti-Gata3 (SC-268) from Santa Cruz Biotechnology.…”
Section: Chromatin Immunoprecipitation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Altered T-cell phenotype in CD4-cre 1 Runx3 F/F , CD4-cre 1 ThPok F/F and CD4-cre 1 Runx3 F/F ThPok F/F mice The conventional T-cell fate model has indicated that ThPok is barely detectable in CD8 1 T cells, 22,38 and Runx3 expression in turn is decreased in CD4 1 T cells. 39,40 However, our real-time PCR analyses revealed that Runx3 and ThPok were both expressed in the CD4 1 and DN subsets of iNKT cells, whereas a low abundance of Runx1 mRNA was detected ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has revealed that transcription factors c-Myb, Gata3, Tox, and cKrox (also known as Thpok or Zbtb7b) act as CD4 lineage-specifying factors [6][7][8][9][10][11][12][13], whereas Runx3 is required for CD8 lineage differentiation [14,15]. Runx3 has dual functions during CD8 lineage differentiation, where it can act as a repressor by binding to the cis-regulatory silencer elements of the Cd4 and Zbtb7b gene locus and as an activator by promoting CD8 lineage-related gene expression [15][16][17][18]. However, the mechanisms by which these lineage-specifying factors are regulated remain largely unknown.…”
Section: Cd8mentioning
confidence: 99%